Result of tensor fascia lata muscle pedicle bone graft in early-stage avascular necrosis of femoral head in adults - Pal, Dilip Kumar; Singh, Animesh Kumar; Kundu, Pranay; Aryan , Anshu (International Journal of Research in Orthopaedics, 2025)
Background: The avascular necrosis (AVN) of femoral head in young adults is a disabling condition. The core decompression along with Tensor fascia lata (TFL) Muscle pedicle bone graft (MPBG) fixed with screw at the base of the neck of the femur is a simple, effective, treatment method with excellent to good result in majority of the early cases of AVN. Methods: In this retrospective study we operated on 32 hips with early or advanced AVN especially in young adults from May 2021 to April 2023, using core decompression along with TFL MPBG fixed with screw at the base of the neck of the femur. The final assessment was done on only those patients who were followed for at least 2 years post operatively using modified Harris hip score (mHHS). Results: The mean age of the patients was 29.2 years. The mean duration of surgery was 129 minutes. The mHHS score was found to be excellent in 12, good in 15, Fair in 3 and poor in 2 patients. The correlation was found between AVN & mHHS. Those with early AVN had better mHHS compared to advanced one, whereas a few with advanced AVN had the tendency to progress to further advanced stage of AVN. Conclusions: The core decompression along with TFL MPBG fixed with screw in the neck of the femur is a simple, effective and reproducible treatment modality with excellent to good results in early AVN in majority of young adults.